MASHALIH AL-ANFUS DALAM KONTEN EDUKASI KESEHATAN MENTAL PADA INSTAGRAM @STUDIODJIWA - Amatullah, Wafa; Fanshoby, Muhammad (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2024)
The role of social media for teenagers is related to psychological impacts, including mental health problems. As a social media platform that is popular to used, Instagram has become an educational platform for its users, one of which is as a medium for mental health education. One of the psychoeducational accounts that uses Instagram social media as a means to build awareness of the importance of mental health is Studio Jiwa. The use of social media in the health sector has shown the urgency in providing accurate and up-to-date health information. The thoughts of religious figures also have the potential to provide valuable insight into mental health. One of them is the thoughts of Abu Zayd Al-Balkhi in his work Mashâlih al-Abdân wa al-Anfus. This research aims to answer the problem formulation of how to analyze the content of @studiodjiwa Instagram content according to Philipp Mayring's Qualitative Content Analysis theory and the dominant message indicators in @studiodjiwa Instagram content. The research uses a qualitative approach. The technique used to obtain the data needed in this research is by observing and documenting. Then, to analyze Studio Jiwa's content, Philipp Mayring's qualitative content analysis theory was used. The results of the research show that there are 7 contents from 14 November 2023 to 11 April 2024, of which 5 contents are included in the indicator category for maintaining Al-Balkhi's mental health internally, and 2 contents maintain health externally. Meanwhile, the dominant message indicator in @studiodjiwa Instagram content is an indicator of maintaining mental health internally.